Seroprevalence of hepatitis b and c viruses in blood donors in a third level hospital from 2019 to 2023. - Karina Cazarin-Chávez; Yadira L. Béjar-Ramírez; José A. Pérez-González; Claudia G. Solís-Hernández; María F. Higuera-De la Tijera; José L. Pérez-Hernández (Annals of Hepatology)
Introduction and Objectives: Hepatitis B virus (HBV) and C virus (HCV) infection are public health problems and risks for transfusion medicine, which have been reduced by routine serological screening. The aim of this work is to describe the prevalence of these infections in blood donors in a tertiary hospital. Materials and Patients: An observational, descriptive, retrospective and analytical study was conducted from 2019 to 2023 in blood donors in a third-level hospital, a total of 99,393 donors; only the complete records of the donors who resulted with reactivity and later confirmation for HBV and HCV were reviewed, The data were analyzed using the Statistical Program SPSS. Qualitative variables are expressed as percentages and quantitative variables as mean±SD, as appropriate. Results: A total of 370 donors who tested positive for some virus were included, despite having been classified as suitable to donate blood products following an official questionnaire with no relevant history and laboratory tests with no alterations. The mean age was 42.02±11.88 years; 54% were men; 135 patients were reactive for HBV and 235 for HCV; however, the true seropositivity found was 2 (1.4%) cases with HBV and 11 (4.6%) cases for HCV (figure 1); the rest of the donors with reactive serology had negative confirmatory studies. The overall seroprevalence observed in our population was 0.002% for HBV, 100% for men and, 0.011% for HCV, 45.4% for women and 54.4% for men. The frequency was 5.5 times higher for HCV than for HBV. Conclusions: In people with no apparent risk factors, the prevalence of HBV and HCV infection is very low, with HCV being more frequent. However, if the “fit” is infected, it is necessary to optimize the health system to offer universal screening that includes those with risk factors.